Pengaruh Customer Engagement dan Pemanfaatan Teknologi BRImo Terhadap Kepuasan Serta Dampaknya Pada Loyalitas Nasabah Bank BRI Kantor Cabang Jelambar: Customer Engagement dan Pemanfaata Teknologi BRimo - mochamad pajar kurnia (J-MD Jurnal Manajemen Dakwah, 2022)
The purpose of this study was to examine and analyze the effect of customer engagement and the use of technology on customer loyalty and customer satisfaction as a mediating variable. The object of this research is the customer of Bank BRI Jalembar Branch Office. The research method used is explanatory research. with the method of determining the sample is purposive sampling with a sample of 100 people. Methods of data collection using online questionnaires and data analysis techniques using SEM-PLS with WarpPLS 6.0 software. The results showed that customer engagement has a significant effect on customer satisfaction. While the use of information technology has no significant effect on customer satisfaction. Customer engagement and customer satisfaction have a significant effect on customer loyalty. While the use of information technology has no significant effect on customer loyalty.